2016
DOI: 10.1038/onc.2016.273
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic carcinoma-associated fibroblasts enhance immune suppression by facilitating the generation of myeloid-derived suppressor cells

Abstract: A major barrier to effective cancer immunotherapy is immune suppression in favor of tumor progression. Additionally, the accumulation of myeloid-derived suppressor cells (MDSCs) has recently been recognized as a major mechanism of the promotion of immune suppression. However, how MDSCs are induced and the cells from which they arise remains unknown. Although studies have demonstrated that tumor-derived cytokines promote MDSC accumulation and activation, little is known regarding the role of the tumor stroma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 47 publications
3
131
0
Order By: Relevance
“…Though the immunosuppressive environment formed by liver reduced the antigen recognition by immune cells (Jakab, 2015), but on the contrary, hindered the recognition of mutational cells. Homoplastically, tumor-induced MDSCs could significantly promote progression of tumor, by elaborately establishing immunosuppressive environment (Deng et al, 2017). According to surface markers, MDSCs in mice could be divided into the granulocytic and monocytic MDSC, both which possessed strong immunosuppressive ability (Fleming et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Though the immunosuppressive environment formed by liver reduced the antigen recognition by immune cells (Jakab, 2015), but on the contrary, hindered the recognition of mutational cells. Homoplastically, tumor-induced MDSCs could significantly promote progression of tumor, by elaborately establishing immunosuppressive environment (Deng et al, 2017). According to surface markers, MDSCs in mice could be divided into the granulocytic and monocytic MDSC, both which possessed strong immunosuppressive ability (Fleming et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…73 CAFs could attract monocytes and further differentiate them into MDSCs via activating STAT3 mediated by IL-6, which creating an immunosuppression microenvironment by inhibiting T cell proliferation in hepatocellular carcinoma. 74 Yang et al reported that FAP + CAFs secreted CCL2 to promote tumour growth via the recruitment of MDSCs in a murine liver tumour model. 75 Multiple studies have shown an anti-tumour effect of inhibiting the colony-stimulating factor 1 receptor (CSF1R).…”
Section: Interaction Between Cancer-associated Fibroblasts and Myelmentioning
confidence: 99%
“…Interestingly enough CAFs, which in the present study were significantly enriched with IL-6-positive stromal cells particularly in advanced and poorly differentiated HCCs, have been recently shown to make the HCC microenvironment more tolerogenic, by inducing the generation of myeloid-derived suppressor cells through IL-6-mediated STAT3 activation. These data suggest that the “in situ” analysis of the interaction between hepatic cancer cells and those of the tumoral stroma like CAFs, might be of help in the future to discern HCC with distinct tolerogenic features, for potential therapeutic applications [26]. …”
Section: Discussionmentioning
confidence: 99%